Volatile and phenolic composition of monovarietal red wines of Valpolicella appellations - Davide Slaghenaufi; Enrico Peruch; Marco De Cosmi; Léa Nouvelet; Maurizio Ugliano (OENO One, 2021)
Volatile and phenolic compositions of nine monovarietal wines from varieties allowed in the Valpolicella appellation have been investigated, including Corvina, Corvinone, Rondinella, Molinara, Oseleta, Raboso, Croatina, Sangiovese and Cabernet Sauvignon. Different clones were also investigated for Corvina and Corvinone, the two main varieties of the appellation. All grapes were harvested from a single experimental block and vinified using a standard protocol. Wines from different clones of Corvina were characterized for higher monoterpenols content, including linalool, α-terpineol and geraniol as well as by a peculiar pattern of C6-alcohols. Relatively high levels of monoterpene alcohols have been found also in Corvinone wines, while Oseleta showed the highest concentration of terpinen-4-ol and cis- and trans- isomers of linalool oxide. Evaluation of wine aroma profile by means of aromatic series indicated higher values for the “floral”, “fruity” and “ripe fruit” series for Corvina and Corvinone wines. Phenolic composition highlighted major differences among wines of different varieties. Total phenolics and total tannins values of Corvina, Corvinone, Rondinella and Molinara wines indicated relatively low phenolic content in comparison with Croatina, Oseleta, Cabernet Sauvignon. Content of individual phenolic compounds, in particular anthocyanins, also highlighted major differences among the monovarietal wines.